Biomechanical gait effects of a single intervention with wearable closed loop control FES system in chronic stroke patients. A proof-of-concept pilot study - Hosiasson, M.; Rigotti-Thompson, M.; Appelgren-Gonzalez, J. P.; Covarrubias-Escudero, F.; Urzua, B.; Barria, P.; Aguilar, R. (My University, 2023)
Foot drop is a gait disturbance characterized by difficulty in performing ankle dorsiflexion during the swing phase of the gait cycle. Current available evidence shows that functional electrical stimulation (FES) on the musculature responsible for dorsal ankle flexion during gait can have positive effects on walking ability. This study aims to present a proof of concept for a novel easy-to-use FES system and evaluates the biomechanical effects during gait in stroke patients, compared to unassisted walking. Gait was quantitatively evaluated in a movement analysis laboratory for five subjects with chronic stroke, in basal condition without assistance and in gait assisted with FES. Improvements were found in all temporospatial parameters during FES-assisted gait, evidenced by statistically significant differences only in gait speed (p=0.02). Joint kinematics showed positive changes in hip abduction and ankle dorsiflexion variables during the swing phase of the gait cycle. No significant differences were found in the Gait Deviation Index. In conclusion, the present pilot study demonstrates that the use of this FES system in the tibialis anterior muscle can cause gait functional improvements in subjects with foot drop due to chronic stroke.
Keywords: Functional electrical stimulation; Foot drop; Stroke